Human Rights and Latina Feminisms: Implications for Clinical Practice with the Latine Diaspora in Anti-immigrant Times. - Villarreal Sosa, Leticia; Castillo Martinez, Miriam (Clinical Social Work Journal, 2025)
In the anti-immigrant context, the Latine community experiences particular challenges as they are prime targets of racism and xenophobia. The social construction of immigrants as a "threat" and "criminals" shapes political responses to migration and allows for the use of extreme practices, such as long detention periods, inhumane conditions, and other violations of human rights. As clinical social workers, a focus on the political and social context means that interventions can both be tailored to the individual or family's particular lived experience and focus on changing the structural conditions that create trauma. This article highlights several theoretical and global perspectives necessary for clinical social workers to adequately meet the needs of Latine service users in the United States. These perspectives recognize and leverage the strengths of the Latine community and consider how the social context may impact individuals and families. Specifically, clinical social work practice grounded human rights, ethics, critical theories including an intersectional Latina feminist perspective, and an understanding of historical trauma will be discussed.